Study on the changes in the microbiome before and after seed embryo after-ripening of Fritillaria cirrhosa - Li, Wenshang; Zhao, Can; Tao, Qian; Zhang, Weimin; Wang, Hai; Han, Guiqi; Yan, Zhuyun (Frontiers in Plant Science, 2025)
IntroductionMicroorganisms play an important role in the embryonic development of plant seeds; however, there are no existing reports on the microbial communities associated with Fritillaria cirrhosa before and after embryo after-ripening.MethodsIn this study, the microbial communities of Fritillaria cirrhosa seeds before and after after-ripening were analyzed using the Illumina MiSeq platform, targeting the V4–V5 region of the bacterial 16S rRNA gene and the ITS1 and ITS2 regions of fungal ribosomal RNA.ResultsThe results showed that bacterial communities were more susceptible to environmental stress and exhibited greater fluctuations compared to fungal communities, as reflected in higher diversity and significant changes in the relative abundance of dominant genera and species. After embryo after-ripening, the dominant fungal genera were Botrytis (SBAR, 29.35%), Tetracladium (SBAR, 15.86%), Ilyonectria (SBAR, 15.35%), and Mrakia (SBAR, 13.14%), while the dominant bacterial genera were Pseudomonas (SBAR, 26.69%) and Stenotrophomonas (SBAR, 16.30%).Prediction results suggested that the bacterial communities with sharply increased relative abundance after embryo after-ripening may interact with seeds through various pathways, including carbohydrate metabolism, absorption and utilization of nitrogen (N), sulfur (S), phosphorus (P), and iron (Fe), as well as secretion of antibiotics, vitamins, cytokinins, and amino acids. Functional validation revealed that most culturable fungi with sharply increased relative abundance had cellulase-degrading abilities, while most of the bacterial isolates were capable of absorbing and utilizing C, N, S, P, and Fe elements. Microbial co-occurrence network analysis indicated that the microbiome after embryo after-ripening formed an unstable, expansive, and rapidly changing network.DiscussionIn summary, this study revealed the overall dynamics of the microbiome in Fritillaria cirrhosa seeds after embryo after-ripening and identified key microbial taxa exhibiting sharp shifts in relative abundance. This work provides a foundational understanding of the microbial succession associated with seed embryo after-ripening in Fritillaria cirrhosa, which may support seed after-ripening and germination, and enhance seed stress resistance.